ASSESSMENT OF SOIL CHARACTERISTICS AND HEAVY METAL POLLUTION IN A SEMI-ARID REGION OF NORTHEAST ALGERIA - Rania Gacem; Hana Souahi (Revista de Agricultura Neotropical)
Dynamics of heavy metal pollution in soil is crucial for devising effective measures to address its negative impacts. The purpose of this study is to assess the concentration of heavy metals in soil in a semi-arid area and to evaluate the effects of these metals on the environment. Sampling of soil occurs at 15 sites spanning over the study area. Each site covers an area of 100 m2. Composite soil samples are then composed, each comprising five individual samples collected from each site. The study evaluates various physicochemical soil parameters, including potential hydrogen (pH), electrical conductivity (EC), organic matter (OM), soil texture, calcium carbonate (CaCO3), soil nutrients, and the level of heavy metal (lead (Pb), copper (Cu), zinc (Zn), iron (Fe), and Cadmium (Cd)) toxicity in soils. After analyzing our data, we found that the soil samples are characterized by moderate pH levels. It ranges from 7.08 ± 0.07 to 7.71 ± 0.25. It also is character iced by a salinity of soil from 1740.00 to 1270.33 μS cm-1, low organic matter content from 0.26 % ± 0.06 to 0.44 % ± 0.14, and a moderate presence of calcium carbonate between 32.16% ± 2.36 and 45.16% ± 3.51. The Cd concentrations in agricultural soils have exceeded background values; it varied from 1.83 mg kg-1 ± 0.28 to 6.50 mg kg-1 ± 0.50 indicating ecological danger. The findings underscore the importance of continuous monitoring and remediation efforts to mitigate the negative effects of heavy metal pollution on soil quality and, consequently, on the environment and human health.